Analisis Kriteria Kesahihan Matan dalam Hadis: Kajian Teori dan Metodologi - Hikmah, Nur; Pangestu, Satrio Anugrah; Luthfia, Nisha (Journal of Hadith Studies, 2023)
The issue of hadith authenticity, particularly among Orientalist scholars, has generated a critical and controversial discourse. Prophetic hadith is often perceived as irrelevant to contemporary realities, largely due to the socio-cultural and environmental contexts in which it originated. This situation highlights the need for focused studies on matn (textual) criticism to identify the core criteria most commonly used in assessing the authenticity of hadith texts. This study addresses two main questions: (1) Have the criteria for matn authenticity evolved? and (2) How can these criteria be applied to contemporary issues? The research employs a Systematic Literature Review (SLR) method, based on journal articles and books published between 2015 and 2023. Sources were collected using keywords such as “matn criticism” and “textual authenticity,” retrieved from Google Scholar and Semantic Scholar, then analyzed and displayed in tabular form. The findings indicate a notable evolution in methodological approaches and perspectives on hadith authenticity. Scholars have increasingly adopted contextual and hermeneutical frameworks to interpret hadith in light of current socio-historical realities. The debate on the validity of hadith texts also reflects shifting views on canonical collections like Ṣaḥīḥ al-Bukhārī and Ṣaḥīḥ Muslim. These developments illustrate the methodological diversity and the ongoing efforts to reinterpret Islamic intellectual heritage in a way that responds to modern challenges.